Covidku Amati-Tuliskan-Kampeyakan Dalam Pembelajaran PPKN Pada Masa Pandemi Siswa Kelas 4 SD Negeri Bawang 3 Kota Kediri - Nur, Nur Lailiyah; Dewi Sholihatur Rohmah (Efektor, 2022)
This study aims to produce technology-based PPKn learning media innovations, especially Powerpoint media for SDN Bawang 3 students in Kediri. This research also seeks to increase students’ interest and motivation to learn, improve learning outcomes, and instill independent character. PowerPoint media innovation has three working mechanisms: observe, write, and campaign. The learning media innovation development model used in this study is the Lee & Owens model. The Lee & Owens model steps start from the stages of problem analysis, planning, development, implementation, and evaluation. The results of this study can increase students' motivation, activeness in learning and make learning more meaningful so that students can apply it in everyday life and train students' courage; this is proven by students being able to campaign for ways to save energy in everyday life in the form of videos.